Zum Lautwert einiger Hieroglyphen - Schweitzer, Simon D. (Zeitschrift für ägyptische Sprache und Altertumskunde, 2011)
This article examines the sound value of four hieroglyphs ([D1], [U23], [F25] and [W19]): They have to be read in the following way: [D1] as tp and not as dp , Dp or Tp , [U23] as mr and not as mHr , [F25] as whm and not as wHm and [W19] as mj and not as mr .